Methanol production from steel-work off-gases and biomass based synthesis gas - Lundgren, J.; Ekbom, T.; Hulteberg, C.; Larsson, M.; Grip, C.-E.; Nilsson, L.; Tunå, P.
Off-gases generated during steelmaking are to a large extent used as fuels in process units within the plant. The surplus gases are commonly supplied to a plant for combined heat and power production. The main objective of this study has been to techno-economically investigate the feasibility of an innovative way of producing methanol from these off-gases, thereby upgrading the economic value of the gases. Cases analyzed have included both off-gases only and mixes with synthesis gas, based on 300MWth of biomass. The SSAB steel plant in the town of Luleå, Sweden has been used as a basis. The studied biomass gasification technology is based on a fluidized-bed gasification technology, where the production capacity is determined from case to case coupled to the heat production required to satisfy the local district heating demand. Critical factors are the integration of the gases with availability to the synthesis unit, to balance the steam system of the biorefinery and to meet the district heat demand of Luleå. The annual production potential of methanol, the overall energy efficiency, the methanol production cost and the environmental effect have been assessed for each case. Depending on case, in the range of 102,000–287,000ton of methanol can be produced per year at production costs in the range of 0.80–1.1EUR per liter petrol equivalent at assumed conditions. The overall energy efficiency of the plant increases in all the cases, up to nearly 14%-units on an annual average, due to a more effective utilization of the off-gases. The main conclusion is that integrating methanol production in a steel plant can be made economically feasible and may result in environmental benefits as well as energy efficiency improvements. Methanol production; Steel work off-gases; Biomass gasification; Steel plant;